2012
DOI: 10.1016/j.neurobiolaging.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Hormone levels and cognitive function in postmenopausal midlife women

Abstract: Gonadal hormones may influence cognitive function. Postmenopausal midlife women in the populationbased Melbourne Women's Midlife Health Project cohort were administered a comprehensive battery of neuropsychological tests on two occasions two years apart. Participants (n=148, mean age 60 years) had undergone natural menopause and were not using hormone therapy. Estrone, total and free estradiol, and total and free testosterone levels were measured at time of the first testing. Principal component analysis ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 60 publications
7
34
0
8
Order By: Relevance
“…However, the excess of testosterone is also linked to adverse cognitive outcomes, as demonstrated in the study of Ryan et al a population of 148 women, where a relative androgen excess in midlife was negatively associated with performance on tasks of semantic and verbal episodic memory [59].…”
Section: Observational Studiesmentioning
confidence: 99%
“…However, the excess of testosterone is also linked to adverse cognitive outcomes, as demonstrated in the study of Ryan et al a population of 148 women, where a relative androgen excess in midlife was negatively associated with performance on tasks of semantic and verbal episodic memory [59].…”
Section: Observational Studiesmentioning
confidence: 99%
“…15,32,33 In early postmenopause, greater endogenous estradiol has been associated with better cognitive performance in semantic memory. 34 Further, longer reproductive periods (indicating greater exposure to endogenous estrogens) are associated with better immediate and delayed verbal memory in mid-to-late life postmenopausal women. 35,36 A review of neuropsychological studies in women age >60 years found that higher estradiol levels were associated with better memory performance across multiple domains, including episodic and semantic memory.…”
Section: Introductionmentioning
confidence: 96%
“…At baseline and 2-year follow-up testing, self-reported current hormone therapy, smoking status, weekly alcohol intake and mood (using the 10-item Center for Epidemiological Studies Depression Scale [23]) were collected. Free oestradiol and testosterone were measured using fasting morning blood samples at the time of baseline testing as described elsewhere [24]. …”
Section: Methodsmentioning
confidence: 99%